A influência da dimensão ambiental na atitude, na intenção de compra e no desejo de pagar pela carne bovina - Burnier, Pedro Carvalho (2018)
Sustainable consumption may be the result of a decision-making process that considers not only the individual needs of consumers (related to taste, price and convenience), but also perceptions and attitudes towards social responsibility (environment and fair trade), labeling (brand and seal) and sustainable food production (traceability, CO2 emissions and animal welfare). Sustainable products tend to be perceived by consumers as having higher quality and greater social, environmental and economic value. The beef sector must be aware of consumer behavior to improve sustainability in order to both take actions and comply with legislation to meet these demands. This study assesses the influence of the environmental dimension on the attitude, intention to buy, willingness to pay, involvement, concern over the production process and with the quality of the beef. Formatted in articles, this dissertation is divided into three chapters. First, a qualitative study was conducted (in-depth interviews with specialists and consumer focus groups) aiming at mapping the dimensions to relevant socio-environmental attributes that influence consumers’ purchasing attitudes and intentions. Then an online survey was conducted with 725 consumers of meat, a structural model was proposed, and 8 hypotheses were tested using the software SmartPLS-3.0 to analyze the relations between the proposed constructs from the literature review so as to establish a scale to measure the concern with the production process. Finally, the consumer’s intention to buy and willingness to pay were tested, taking into account only trade-offs of socio-environmental attributes of beef based on a model of Discrete Choice Analysis. The results obtained from both the in-depth and focus groups interviews in the first article aimed at validating the relevance of variables included in the proposed conceptual model bearing relations that may assess the influence of the environmental dimension on the attitude towards and intention of purchasing beef. The model tested in the second article suggests that involvement with product and concern over production process are related to attitude towards and intention of purchasing sustainable meat. However, brand value (which includes food safety) is not correlated with sustainable meat purchasing intention. The scale that measures the concern over the production process shows that the attributes of animal welfare, traceability, company’s social and environmental responsibility should be better communicated to consumers. Finally, the results obtained in the third article confirm the importance of both animal welfare and traceability attributes upon choosing meat. The study indicates that consumption frequency, type and presence of a known brand distinctively influence meat choice on a functional purchase (day to day) when compared to a hedonic purchase (barbecue). The results suggest that industry and retailers should better explore the opportunity for differentiation, increasing knowledge about carbon emissions and disseminating the animal welfare attribute in the language of their communication strategies and product / brand positioning which have socio-environmental attributes as part of the benefits to the final consumer. The proposed structural model should be used as a reference in future studies that include food sustainability as a theme. The devised and validated scale that comprises the Concern over the Production Process construct should be used as a reference in future studies. Investigating the trade-offs between socio-environmental attributes gives way to assessing them more profoundly and contributes to the extant literature.